Kualitas Serbuk Gergaji yang Difermentasi menggunakan Jamur Trichoderma viride - Lutojo Lutojo (Caraka Tani: Journal of Sustainable Agriculture, 2005)
Amount of 18 bag sacks of sawdust have been used to know the influence of sawdust fermentation with Trichoderma viride on nutrition quality. Randomized complete block design of factorial 2x3 used as the experiment design in this research. First factor consist of 2 old level of ferment (10 and 20 day) and second factor consisting of 3 inoculums dose level (2, 3 and 4%). Variable observed are dry matter degradation, change of protein and fiber contains.The result showed that dry matter degradation increased when inoculums dose and ferment time increased too. The most loss of dry matter got at 4% of inoculums dose (5,65%) and at 20 days ferment time (4,77%). The effect of inoculums dose is significant increasing protein containt. Highest increase got at 4% inoculums dose (169,12%) and the lowest at 2% (49,56%).There are interaction influence from both factor to the degradation of fibre contains on sawdust fermentation. At all of used inoculums dose fibre contains downhill in line with the increasing of ferment time and inoculums dose. The lowest degradation obtained at 2% treatment combination.Conclusion from this research is that more and more inoculums dose and time ferment hence more and more dry matter degradation, increasing protein and downhill fibre contains.